2013
DOI: 10.1007/s00345-013-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde and CA II autoantibody levels are elevated in children with undescended testes

Abstract: MDA is the most reliable and decisive biochemical marker displaying oxidative damage in undescended testes, and an autoimmune response may be triggered by oxidative stress against CA II during the UDT process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Many studies reported that the MDA levels in UDT group were significantly higher than that of the healthy control group. 2,5 Our results showed that lipid peroxidation increased in children with UDT. With the prolonged temperature exposure time of the testicle, the oxidative damage can increase.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Many studies reported that the MDA levels in UDT group were significantly higher than that of the healthy control group. 2,5 Our results showed that lipid peroxidation increased in children with UDT. With the prolonged temperature exposure time of the testicle, the oxidative damage can increase.…”
Section: Discussionmentioning
confidence: 52%
“…They also stated that testicular torsion is an acute condition, but UDT is a chronic condition. 2 In one study, the rat testicle was torsioned and the two groups were formed as 2 and 4 hours after torsion. The IMA level in the group 4 hours after torsion was significantly higher than sham group and the group 2 hours after torsion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDA levels in erythrocytes were determined as described in a previous publication (Agilent 1100 series HPLC systems, Waldbronn, Germany), C18 column was used for measurements (ZORBAX Eclipse XDB-C18; 4.6 x 150mm; Agilent Technologies, Santa Clara, CA, USA) [12]. Detection was performed fluorometrically (excitation 536 nm and emission 555 nm).…”
Section: Determination Of Malondialdehyde (Mda) Levels In Erythrocytesmentioning
confidence: 99%
“…Similar publications in the literature did not support this issue with postoperative period values. 2,3 Due to lack of cases, budget, and time limitations, the aforementioned deficiencies may not have been covered; therefore, this issue should be addressed by further studies and samples of testicular tissue itself rather than only blood samples.…”
mentioning
confidence: 99%